Thresholded overlapping of images - Montenegro Joo, Javier (2012)
An algorithm to select a set of pixels above a predefined grey-level threshold from an image, extract it and transfer it to another image is presented; the result is a restricted overlapping of images, based on the Controlled (modulated) image difference technique. In some applications this thresholded overlapping may be an option to consider when the aim is the mixture of images.